Substitutions in Spike and Nucleocapsid proteins of SARS-CoV-2 circulating in South America (2020)
SARS-CoV-2 is a new member of the genus Betacoronavirus, responsible for the COVID-19 pandemic. The virus crossed the species barrier and established in the human population taking advantage of the spike protein high affinity for the ACE receptor to infect the lower respiratory tract. The Nucleocapsid (N) and Spike (S) are highly immunogenic structural proteins and most commercial COVID-19 diagnostic assays target these proteins. In anunpredictable epidemic, it is essential to know about their genetic variability. The objective of this study was to describe the substitution frequency of the S and N proteins of SARS-CoV-2 in South America. A total of 504 amino acid and nucleotide sequences of the S and N proteins of SARS-CoV-2 from seven South American countries (Argentina, Brazil, Chile, Ecuador, Peru, Uruguay, and Colombia), reported as of June 3, and corresponding to samples collected between March and April 2020, were compared through substitution matrices using the Muscle algorithm. Forty-three sequences from 13 Colombian departments were obtained in this study using the Oxford Nanopore and Illumina MiSeq technologies, following the amplicon-based ARTIC network protocol. The substitutions D614G in S and R203K/G204R in N were the most frequent in South America, observed in 83% and 34% of the sequences respectively. Strikingly, genomes with the conserved position D614 were almost completely replaced by genomes with the G614 substitution between March to April 2020. A similar replacement pattern was observed with R203K/G204R although more marked in Chile, Argentina and Brazil, suggesting similar introduction history and/or control strategies of SARS-CoV-2 in these countries. It is necessary to continue with the genomic surveillance of S and N proteins during the SARS-CoV-2 pandemic as this information can be useful for developing vaccines, therapeutics and diagnostic tests.